Magnetic nanoparticles of Nd2Fe14B prepared by ethanol-assisted wet ball milling technique - Younes Mehrifar; Hamed Moqtaderi; Seyedeh Mehri Hamidi; Farideh Golbabaei; Mahdi Hasanzadeh; Somayeh Farhang Dehghan (Scientific Reports)
Abstract The magnetic material Nd2Fe14B is one of the strongest magnetic materials found in nature. The demand for the production of these nanoparticles is significantly high due to their exceptional properties. The aim of the present study is to synthesize magnetic nanoparticles of Nd2Fe14B using ethanol in the wet ball milling technique (WBMT). Nd2Fe14B powder an average particle size(APS) of 730 nm was subjected to wet ball milling in stainless steel cup containing 5 mm diameter steel balls.The powder was milled for 12 h at 400 rpm, with intervals of 15 min and a 15-second pause each time. The morphology of the powder and nanoparticles, crystallinity, changes of the samples under temperature, magnetic properties, and the structural bonds were analyzed using field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA), vibrating sample magnetometry (VSM), and Fourier-transform infrared spectroscopy (FTIR).The microstructural images revealed that the shape of the particles changed from flat(730 nm) to spherical(76 nm) after WBMT. The crystallinity results indicated a hexagonal crystal structure, with the average crystallite size being 17.1 nm. In the spectrum of the synthesized Nd2Fe14B nanoparticles, a peak appeared at a wavenumber of 803 cm−1, along with peaks at wavenumbers of 1037 cm−1 and 1083 cm−1, which are associated with the stretching vibrations of Nd-Fe, Fe-B, and Nd-B bonds, respectively. Numerical results of magnetic performance parameters indicated the ferromagnetic properties of the particles(HC = 6097.47, Mr = 34.65 and MS = 49.11).It appears that in WBMT, the operational parameters significantly affect the average crystallite size, saturation magnetization, as well as the size and shape of the nanoparticles. Additionally, the ferromagnetic nature of Nd2Fe14B in the hysteresis loop plays an important role in the thermal stability of the nanoparticles.